a Model Of Adolescent Ethics In Mobile Diffusion On The Use Of Cellphones And Social Media In Semarang City - Pertiwi Putri, Arfika; Siregar, Nadia Itona (ETTISAL : Journal of Communication, 2023)
The Central Statistics Agency (BPS) notes that in 2022 as many as 67.88% of Indonesia's population aged over 5th years have a mobile phone. Meanwhile, in the same year, it was recorded that 65.15% of the people of Central Java Province owned cell phones. Some factors play an essential role in shaping adolescents' ethical views regarding mobile phones and social media use. This study aimed to analyze the factors that influence ethics by using mobile phones and social media in adolescents aged 13-15 years in Semarang. This study uses a quantitative method with Partial Least Squares (PLS) analysis. The theory used in this study is the theory of Uses and Gratification, Diffusion Innovation of Technology, and Ethical Systems. Primary data was obtained by distributing questionnaires to 100 respondents. The sampling technique used with the method of accidental sampling. The study results show a relationship between adolescents' mobile phone use and social media use by adolescents with the social interaction they receive. Active involvement in online interactions can have an impact on adolescent ethics, this is reflected in aspects of self-satisfaction. Besides that, emotional satisfaction factors such as feelings of pleasure and satisfaction in online interactions affect the formation of adolescent ethics. This study also reveals that the ethical model of adolescents is influenced by two main dimensions, namely fairness and utilitarian ethics. The implications of these findings can be used for the development of better educational approaches in teaching youth about ethics and responsibility in using technology and interacting in a digital environment.